Calidad estructural de las viviendas de albañilería confinada en el barrio Higos Urco, Chachapoyas, 2018 - Arteaga Ynfante, Rey Euler (2022)
In the Amazonas region as well as throughout the country, self-construction continues to be practiced, a practice that directly influences the structural quality of the houses. The purpose of this research was to contribute with alternatives to improve the structural quality of confined masonry houses located in the Higos Urco neighborhood with a sample of 44 houses. For the present study, data were collected through a survey and by diagnosing the current situation of each dwelling in terms of its structure. From this it was determined that 25% of the houses are of very poor quality, 27.3% are of poor quality, 22.3% are of regular quality and 25% are of good quality. For which a booklet was proposed with alternatives for repair, reinforcement and construction of confined masonry houses, the proposed alternatives were developed to improve the structural quality of houses with deficiencies in walls either by failures or by the use of inadequate masonry. It was concluded that the factors with the greatest impact on structural quality are the technical advice in construction, the workmanship and the structural quality of the masonry